Paradox or Mitigation? Childless and Parent Gender Gaps across British, Finnish, and German Wage Distributions - Cooke Lynn Prince; Hägglund Anna Erika; Icardi Rossella (OXFORD UNIV PRESS, 2022)
Part of the welfare paradox is that generous family policies increase private sector employer discrimination particularly against higher-wage women. We argue instead that bundles of generous policies mitigate gender productivity differences among parents, and in turn the discrimination also affecting childless women. We test these assertions by estimating the two gaps across the British, Finnish, and German private sector wage distributions using 2000-2018 panel data and unconditional quantile regression. Because of smaller motherhood penalties below the median, parenthood gaps are smallest in Finland and Germany. In contrast, fatherhood premiums constitute most of the parenthood gap for high-wage German and British women, whereas high-wage British women are disadvantaged by motherhood penalties and fatherhood premiums. The childless gap is also smaller across the bottom of the Finnish and German wage distributions. Overall, our advanced modeling strategy finds strong support for the mitigating effects of generous family policies on gender wage gaps.